Left atrial strain in assessing heart failure with preserved ejection fraction in hypertensive patients - E. S. Mazur; V. V. Mazur; N. D. Bazhenov; O. V. Nilova; T. O. Nikolaeva (Российский кардиологический журнал, 2022)
Aim. To compare the results of diagnosing heart failure with preserved ejection fraction (HFpEF) in patients with hypertension (HTN) according left atrial (LA) strain values with the results obtained using the H2FPEF score and diastolic stress testing (DST).Material and methods. The study included 293 patients with previously established HTN who were examined due to complaints of shortness of breath and/or palpitations (men, 97 (33,5%), mean age, 62,0 (55,0; 67,0) years). All patients underwent transthoracic echocardiography with the assessment of LA strain parameters and probability of HFpEF using the H2FPEF score. Eighty five patients with an intermediate probability of HFpEF underwent DST.Results. A low probability of HFpEF according to the H2FPEF score was registered in 35 (11,9%) patients, uncertain — in 206 (70,3%), high — in 52 (17,7%). DST was negative in 43 (50,6%) and positive in 42 (49,4%) patients with an intermediate probability of HFpEF. LA strain in the reservoir phase in patients with a low probability of HFpEF averaged (median and interquartile interval) 28,0 (23,6; 31,5)%, while in patients with an intermediate probability and negative DST — 24,0 (22,0; 26,8)%, with an intermediate probability and positive DST — 20,0 (18,0; 21,0)%, and with a high probability of HFpEF — 19,6 (16,9; 21,8)%. HFpEF was diagnosed in 94 patients, including 52 with a high probability on the H2FPEF score and 42 with an intermediate probability and positive DST. The diagnosis of HFpEF was ruled out in 78 patients, including 35 with a low probability on the H2FPEF score and 43 with an intermediate probability and negative DST. Further, 172 patients with confirmed or excluded HFpEF were randomly divided into two equal cohorts. In the training cohort, HFpEF was diagnosed in 44 (51,2%) patients, in the validation cohort — in 50 (58,1%). ROC analysis performed on the training cohort for the LA strain in reservoir phase showed AUC of 0,920 (95% confidence interval (CI), 0,842-0,968) and cut-off point of 21,5%. In the training cohort, the results of HFpEF diagnosis using the indicated criterion coincided with those using H2FPEF score and DST in 86,1% (95% CI, 77,2-91,8) of cases. The Cohen’s kappa was 0,721 (95% C,I 0,575-0,868). In the validation cohort, agreement was observed in 84,9% (95% CI 75,8-91,0) of cases with Cohen’s kappa of 0,702 (95% CI 0,553-0,851).Conclusion. In hypertensive patients, the diagnosis of HFpEF made on the basis of a decrease in the LA strain in reservoir phase to ≤21,5%, is in good agreement with the diagnosis made using the H2FPEF score and DST.